Where does the river end? Drivers of spatiotemporal variability in CO2 concentration and flux in the inflow area of a large boreal lake. (19th November 2019) - Chmiel, Hannah E.; Hofmann, Hilmar; Sobek, Sebastian; Efremova, Tatyana; Pasche, Natacha
Abstract: River inflow affects the spatiotemporal variability of carbon dioxide (CO2 ) in the water column of lakes and may locally influence CO2 gas exchange with the atmosphere. However, spatiotemporal CO2 variability at river inflow sites is often unknown leaving estimates of lake‐wide CO2 emission uncertain. Here, we investigated the CO2 concentration and flux variability along a river‐impacted bay and remote sampling locations of Lake Onego. During 3 years, we resolved spatial CO2 gradients between river inflow and central lake and recorded the temporal course of CO2 in the bay from the ice‐covered period to early summer. We found that the river had a major influence on the spatial CO2 variability during ice‐covered periods and contributed ~ 35% to the total amount of CO2 in the bay. The bay was a source of CO2 to the atmosphere at ice‐melt each year emitting 2–15 times the amount as an equally sized area in the central lake. However, there was large interannual variability in the spring CO2 emission from the bay related to differences in discharge and climate that affected the hydrodynamic development of the lake during spring. In early summer, the spatial CO2 variability was unrelated to the river signal but correlated negatively with dissolved oxygen concentrations instead indicating a stronger biological control on CO2 . Our study reveals a large variability of CO2 and its drivers at river inflow sites at the seasonal and at the interannual time scale. Understanding these dynamics is essential for predicting lake‐wide CO2 fluxes more accurately under a warming climate.